Effects of Glyphosate on Cognitive Development, Sensory Sensitivity and Locomotor Balance in Male Rats - Fadillah, Fadillah; Irwan , Reziq Marchellino; Afif , Muhamad; Tofrizal , Allimuddin; Zuhir, Elvina; Maliza, Rita (Jurnal Biologi Tropis, 2024)
Glycophate is the active ingredient in RoundupⓇ hebicide, which is commonly used in agriculture. Exposure to the herbicide glyphosate may affect the development of Parkinson Disease in humans. pre-natal and post-natal exposure to glyphosate exerts neurological effects and neuropsychiatric effects, even at low concentrations. This study aimed to examine the effects on cognitive, sensory and motor development in male rats exposed to the active ingredient glycophate in RoundupⓇ at various concentrations. In this study using test animals in the form of male rats with an age of 10 weeks, then the rats were divided into 4 treatment groups, namely the normal group, 100 µL, 50 µL, and 25 µL RoundupⓇ, induction was given orally every day for 4 weeks. Then at the last week, the body weight of the rats was measured and several tests were conducted to see the effect of glycophate induction on rat cognition through the morris water maze and y maze tests, sensory development through the hot plate test, and rat motor development through the hanging wire test. The results showed that glyphosphate administration affected the body weight of the rats, and affected the cognitive development of the rats. The 50 µL dose treatment group showed the most visible effect of glycophosphate exposure on cognitive tests compared to other groups. In the sensory test, the 50 µL ml dose treatment group also had low sensitivity compared to other groups, and low motor ability compared to other groups. Glycophate was seen to affect the cognitive, sensory and motor development of the rats.